2011
DOI: 10.1016/j.immuni.2011.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Pyrin Mutations Induce NLRP3 Protein-Independent Interleukin-1β Activation and Severe Autoinflammation in Mice

Abstract: SUMMARY Missense mutations in the C-terminal B30.2 domain of pyrin cause familial Mediterranean fever (FMF), the most common Mendelian autoinflammatory disease. However, it remains controversial as to whether FMF is due to the loss of an inhibitor of inflammation or to the activity of a proinflammatory molecule. We generated both pyrin-deficient mice and “knockin” mice harboring mutant human B30.2 domains. Homozygous knockin, but not pyrin-deficient, mice exhibited spontaneous bone marrow-dependent inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
370
2
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(404 citation statements)
references
References 34 publications
17
370
2
5
Order By: Relevance
“…We focused on TRIM20 as a TRIM strongly induced by IFN-γ (Carthagena et al, 2009;Chae et al, 2011). We confirmed that TRIM20 expression was responsive to IFN-γ in our system and tested its kinetics and dose-response (Fig.…”
Section: Trim20 Induces Autophagysupporting
confidence: 61%
“…We focused on TRIM20 as a TRIM strongly induced by IFN-γ (Carthagena et al, 2009;Chae et al, 2011). We confirmed that TRIM20 expression was responsive to IFN-γ in our system and tested its kinetics and dose-response (Fig.…”
Section: Trim20 Induces Autophagysupporting
confidence: 61%
“…As a consequence, an inappropriate full-blown inflammation occurs. The activation of IL-1β is mediated by an inflammatory trigger leading to the induction of an inflammasome [27]. TNFalpha plays a role in the mediation of the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Activated inflammasomes are visible as microscopic 'specks' within the cytosol and structural studies have shown that they can polymerize into large oligomers with potentially thousands of subunits [39]. Gain-of-function mutations in the NLRP3 gene are cause de novo and inherited autoinflammatory diseases collectively known as cryopyrin-associated periodic syndromes (CAPS) [40]. Pathogenic mutations, predominantly found in exon 3, affect the NBD within NLRP3 leading to spontaneous oligomerization and a reduced requirement for the second stimulus, ATP, for IL-1secretion after activation by innate immune stimuli [41].…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%